1991
DOI: 10.1002/jnr.490290214
|View full text |Cite
|
Sign up to set email alerts
|

Oligodendrocytes of the jimpy phenotype can be partially restored by environmental factors in vivo

Abstract: Cross-transplantations of neural tissue between jimpy (jp) shiverer (shi) and normal mice have been performed under heterochronic conditions. In all series, fragments of E14-E15 embryonic neural tissue from the different donors have been transplanted into newborn host brain in order to study environmental influences by differentiated tissue on transplanted embryonic cell lines. Large patches of proteolipid protein (PLP)-positive myelin have been observed in the jp brain after transplantation of shi or normal e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

1991
1991
1999
1999

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 30 publications
2
19
0
Order By: Relevance
“…Trophic factors could be supplied by other cells within microenvironments in the mutant CNS, or by replacement conditions in vitro. This theory fits our in vitro observations and would explain both the increased differentiation of jp OLs in heterotypic transplants 26 and the survival and partial differentiation of small numbers of jp OLs in situ. However, studies on transgenic PLP and DM20 knockouts 27,28 indicate that there must also be a dominant-negative consequence of the jp mutation.…”
Section: Jimpy Oligodendrocyte Survival and Differentiation Can Be Ensupporting
confidence: 88%
“…Trophic factors could be supplied by other cells within microenvironments in the mutant CNS, or by replacement conditions in vitro. This theory fits our in vitro observations and would explain both the increased differentiation of jp OLs in heterotypic transplants 26 and the survival and partial differentiation of small numbers of jp OLs in situ. However, studies on transgenic PLP and DM20 knockouts 27,28 indicate that there must also be a dominant-negative consequence of the jp mutation.…”
Section: Jimpy Oligodendrocyte Survival and Differentiation Can Be Ensupporting
confidence: 88%
“…In order to analyse the modalities of these cells activation, their behaviour was studied by immunohistochemistry (IHC) of the myelin they synthesized in the host brain. In addition, these results were compared with results obtained in previous experiments using fragments of PVZ from newborn [18] and embryonic animals [19] as donors.…”
Section: Introductionmentioning
confidence: 90%
“…By contrast these experiments demon strated that the poor myelinating capacity of jp ODCs cannot be modulated by environmental conditions. Fi nally, these experiments suggested that the mitotic poten tial of jp precursor cells transplanted in a newborn envi ronment depends only on their stage of differentiation [18,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggested that PL P gene expression may be related to the secretion of humoral factor(s) that influence maturation and survival of oligodendrocytes. Furthermore, a partial rescue of jimpy oligodendrocytes was observed when embryonic jimpy brain fragments were transplanted into brains expressing a wild-type PLP gene (Lachapelle et al, 1991). Finally, the number of oligodendrocytes present in mixed glial cell cultures containing conditioned media from cell lines expressing the PLP gene (G26 mouse oligodendroglioma, B104 rat neuroblastoma, and B16 mouse melanoma) (Ikenaka et al, 1992) was significantly higher than that of control cultures without conditioned media or those supplemented with conditioned medium from NIH3T3 fibroblasts, which do not produce DM20 (Nakao et al, 1995).…”
Section: Abstract: Oligodendrocyte Development; Myelin Proteolipid Pmentioning
confidence: 99%